A Magnetic Photocatalytic Composite Derived from Waste Rice Noodle and Red Mud - Qing Liu; Wanying Ying; Hailing Gou; Minghui Li; Ke Huang; Renyuan Xu; Guanzhi Ding; Pengyu Wang; Shuoping Chen (Nanomaterials)
This study is the first to convert two waste materials, waste rice noodles (WRN) and red mud (RM), into a low-cost, high-value magnetic photocatalytic composite. WRN was processed via a hydrothermal method to produce a solution containing carbon quantum dots (CQDs). Simultaneously, RM was dissolved in acid to form a Fe3+ ion-rich solution, which was subsequently mixed with the CQDs solution and underwent hydrothermal treatment. During this process, the Fe3+ ions in RM were transformed into the maghemite (γ-Fe2O3) phase, while CQDs were incorporated onto the γ-Fe2O3 surface, resulting in the CQDs/γ-Fe2O3 magnetic photocatalytic composite. Experimental results demonstrated that the WRN-derived CQDs not only facilitated the formation of the magnetic γ-Fe2O3 phase but also promoted a synergistic interaction between CQDs and γ-Fe2O3, enhancing electron-hole pair separation and boosting the production of reactive radicals such as O2·− and ·OH. Under optimized conditions (pH = 8, carbon loading: 10 wt%), the CQDs/γ-Fe2O3 composite exhibited good photocatalytic performance against methylene blue, achieving a 97.6% degradation rate within 480 min and a degradation rate constant of 5.99 × 10−3 min−1, significantly outperforming RM and commercial γ-Fe2O3 powder. Beyond methylene blue, this composite also effectively degraded common organic dyes, including malachite green, methyl violet, basic fuchsin, and rhodamine B, with particularly high efficiency against malachite green, reaching a degradation rate constant of 5.465 × 10−2 min−1. Additionally, due to its soft magnetic properties (saturation magnetization intensity: 16.7 emu/g, residual magnetization intensity: 2.2 emu/g), the material could be conveniently recovered and reused after photocatalytic cycles. Even after 10 cycles, it retained over 98% recovery and 96% photocatalytic degradation efficiency, underscoring its potential for cost-effective, large-scale photocatalytic water purification.